항공사 소셜 미디어 이용 강도가 온라인 구전 의존도와 온라인 구전 수용에 미치는 영향 - 서은주; 박진우; Seo, Eun Ju; Park, Jin-Woo (한국항공운항학회지, 2017)
As many people all over the world increasingly take more time in exchanging with other people or acquiring information on the internet, use of social media becomes a part of their daily lives. A lot of changes of consumer culture, which have been occurring through social media, have significant effects on corporate marketing activities. Since social media's importance to airlines has been continuously increased, this study attempts to examine effects of passengers' uses of social media, who plan to select an airline, on dependence on reliance of electronic word-of mouth(EWOM) and EWOM acceptance. To this end, a questionnaire survey of passengers who use airlines and the airline's social media was conducted, and then effective data of 302 copies were analyzed by using the structural equation modeling. The findings show that social media use intensity has a significant effect on Acceptance of EWOM via reliance of EWOM, while a direct effect of social media use intensity on Acceptance of EWOM is not significant. From this study, it is found that control and management of social media and only EWOM are effective tools for marketing of airline businesses, suggesting that innovative strategies are required to preemptively cope with changes in consumers' behaviors and markets, which continue to evolve.